The Growth Rate of Propagul Rhizophora mucronata On the Intensity of tubes Various Shade In the Concong village In Indragiri Hilir Regency Riau Province - Hoki kurniawan; Aras Mulyadi; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in June-July 2013 in the village of Concong In Indragiri Hilir Riau Province. The method used in this research was a randomized block design (RAK) consisting of 5 treatments and 10 replications thus obtained 50 experimental units. This study aimed to determine the rate of growth of propagules R. mucronata good at various intensities shade. The results showed growth of propagules R. mucronata significant effect on height growth, diameter, survival percentage, number of leaves and total biomass. High growth in most large propagules present in 25% shade intensity is 0,23 cm. Greatest diameter growth found in 25% and 75% shade intensity is 0,006 cm. Highest percentage of life, of all the intensity of shade. Leaf shade intensity is highest at 100% ie 1.3. Propagules greatest total biomass present in 50% shade intensity is 1.3 grams.Keywords: Riau, R. mucronata, Growth, Shade intensity